2012
DOI: 10.4034/pboci.2012.121.02
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de cárie dentária em crianças de seis a 60 meses e fatores associados, Diamantina, Minas Gerais, Brasil

Abstract: Prevalência de cárie dentária em crianças de seis a 60 meses e fatores associados, Diamantina, Minas Gerais, BrasilPrevalence of dental caries in children aged 6 to 60 months and associated factors in Diamantina, Minas Gerais, Brazil Cárie dental; Epidemiologia; Odontopediatria.Objective: The aim of this study was to assess the prevalence of dental caries and associated factors among children aged 6 to 60 months in Diamantina, MG, Brazil. Methods: A cross-sectional study was performed with a representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The age of approximately six months represents a crucial moment for the colonization of streptococcus mutans and lactobacilli, which is when the first teeth erupt, which is usually associated with weaning and the introduction of solid foods; therefore, prevention of the introduction of sugary beverages and foods and oral hygiene are aimed at preventing the establishment of streptococcus mutans in the biofilm [12]. On the other hand, considering the young age of children, caries was detected in 30.7%, which shows the difficulties found by parents for controlling the risk factors [8,10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of approximately six months represents a crucial moment for the colonization of streptococcus mutans and lactobacilli, which is when the first teeth erupt, which is usually associated with weaning and the introduction of solid foods; therefore, prevention of the introduction of sugary beverages and foods and oral hygiene are aimed at preventing the establishment of streptococcus mutans in the biofilm [12]. On the other hand, considering the young age of children, caries was detected in 30.7%, which shows the difficulties found by parents for controlling the risk factors [8,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the beginning of toothbrushing practice has been considered the most determinant factor for early childhood caries, which highlights the role of oral hygiene instruction [5,6], especially when there is nocturnal feeding [7] and high sugar consumption, since sucrose is the substrate for the oral microbiota [2]. Likewise, it was demonstrated that children aged 6-60 months have higher chance of developing caries when presenting poor oral hygiene, frequency of bottle consumption equal to or greater than three times a day and time of use over five months [8].…”
Section: Introductionmentioning
confidence: 99%
“…The feeding practices that may constitute a risk for dental caries and that could be evaluated in this study considering data filled in the medical records of children aged 1-45 months were: breastfeeding, bottle feeding, feeding during sleep, sugar introduction and frequency. It is noteworthy that one or more of these practices have been related in literature with the development of caries in children [1,[4][5][6][7][8][9][10]12,[14][15][16][17]. In a study with children aged 6-60 months with high prevalence of dental caries, the main factors associated with caries development were: age, frequency of consumption and time of bottle use and unsatisfactory oral hygiene [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that one or more of these practices have been related in literature with the development of caries in children [1,[4][5][6][7][8][9][10]12,[14][15][16][17]. In a study with children aged 6-60 months with high prevalence of dental caries, the main factors associated with caries development were: age, frequency of consumption and time of bottle use and unsatisfactory oral hygiene [9]. In another study with high prevalence of severe early childhood caries in preschool children, the risk factors identified were: environmental factors such as public water supply fluoridation below recommended levels, low maternal schooling, male gender, and behavioral factors such as bottle feeding at 30 months of age [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation